PENGUATAN IDENTITAS DAN SEGREGASI SOSIAL KOMUNITAS EKS PENGUNGSI TIMOR TIMUR DI SUKABITETEK, NUSA TENGGARA TIMUR - Soehadha, Moh (Jurnal Sosiologi Reflektif, 2019)
The exodus of East Timorese refugees after the 1999 referendum to Indonesia left a problem till now. International refugee affairs agencies, the Indonesian government, and non-governmental organizations have helped repatriate refugees. But many refugees do not want to return and choose to stay in Indonesia, among them they choose to stay in the border area in Sukabitetek Village, Belu Regency, East Nusa Tenggara. In a study through an ethnographic approach to the former East Timorese refugee community in the following Sukabitetek, it was explained about strengthening identity and social segregation in the interaction between former East Timorese refugees and local people. Resettlement policies for refugees that are top down and tend to pay less attention to the needs of refugees cause social problems, namely land access, economy and education, economic and political commodification, and social conflict.